The Dilemma of Environmental Sustainability: An Analysis of Mining Policy Implementation in the Case of Illegal Gold Mining in West Aceh - Zuhrizal Fadhly; Cut Asmaul Husna (Catalist Indo Publisher, 2025)
Background This study aims to analyze the effectiveness of the implementation of illegal gold mining control policies (PETI) in West Aceh Regency using Van Meter and Van Horn's (1975) policy implementation theory. Although there is a legal basis through West Aceh Qanun Number 1 of 2013 concerning Spatial Planning, practices in the field show weak enforcement and supervision of illegal mining activities. Methods This study uses a qualitative method with a case study approach through interviews, field observations, and policy document analysis. Results The results of the study show that policy implementation is still symbolic and lacks clear operational direction. Weak cross-sector coordination, limited human resources and budgets, and a permissive attitude among policy implementers are the main obstacles to law enforcement. Furthermore, the local government’s economic dependence on illegal mining revenues creates a policy dilemma between economic growth and environmental conservation. This condition reflects structural weaknesses in governance and institutional accountability. Conclusions These findings confirm that the effectiveness of policy implementation in West Aceh is low because it does not yet meet the principles of consistency, coordination, and accountability. This study recommends reformulating evidence-based policies, increasing local resource capacity, and strengthening participatory monitoring systems to achieve sustainable environmental governance.